2014
DOI: 10.1186/1471-2407-14-296
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Helicobacter pylori infection associates with an increased risk of colorectal polyps in African Americans

Abstract: BackgroundGastric Helicobacter pylori (H. pylori) infection and colorectal polyps are more prevalent in African Americans than in the general population. We aimed to investigate whether gastric H. pylori infection is associated with colorectal polyps in African Americans.MethodsMedical records of African Americans, 40 years and older (n = 1256) who underwent bidirectional gastrointestinal endoscopy on the same day were reviewed. H. pylori status was assessed by immunohistochemistry on gastric specimens. Colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 51 publications
(51 reference statements)
1
38
2
1
Order By: Relevance
“…These differences in population characteristics may explain, at least in part, the discrepancies between our results and those of Epplein et al . Previous studies support the idea of differences by study population in the association between H. pylori and colorectal cancer as well as precursors such as polyps and adenomas .…”
Section: Discussioncontrasting
confidence: 64%
“…These differences in population characteristics may explain, at least in part, the discrepancies between our results and those of Epplein et al . Previous studies support the idea of differences by study population in the association between H. pylori and colorectal cancer as well as precursors such as polyps and adenomas .…”
Section: Discussioncontrasting
confidence: 64%
“…H. pylori is a spiral-shaped bacterium that grows in the mucus layer which coats the inside of the human stomach, ultimately causing inflammation in the stomach called gastritis [62]. Further, it turns to ulcers [63, 64], long-lasting anaemia [6567], and growths in the stomach [68, 69], which are more likely to get cancer. H. pylori is mainly spread through contaminated water, food, saliva, or mouth to mouth contacts and possibly transmitted sexually via oral-genital contact [70, 71].…”
Section: Clinical Associationmentioning
confidence: 99%
“…[3,6,8,9,19, Nineteen of them are cross-sectional studies [3, 6, 8, 19, 21-24, 25-28, 30, 31, 35, 37-40], and the remaining eight are case-control studies [9, 29, 32-34, 36, 41, 42]. Serology was utilized as the detection method for H. pylori in 14 studies [8, 9, 21, 23, 25-27, 31-35, 38, 39], pathology in 4 [3,22,40,42], UBT in 4 [6,37], CLO in 6 [19,24,30,36], and combining UBT and CLO in 2 [28,29] A flow chart describing the process of study selection is shown in Figure 1. For the meta-analysis, data were extracted from twenty-seven studies with a total of 68,410 patients, and the pooled OR for colorectal adenoma related to H. pylori infection was 1.51 (95% CI 1.39-1.63), although there was significant heterogeneity (p < 0.001) ( Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%